2021
DOI: 10.1017/jfm.2021.779
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical experiments on turbulent entrainment and mixing of scalars

Abstract: Numerical experiments on the turbulent entrainment and mixing of scalars in a incompressible flow have been performed. These simulations are based on a scale decomposition of the velocity field, thus allowing the establishment from a dynamic point of view of the evolution of scalar fields under the separate action of large-scale coherent motions and small-scale fluctuations. The turbulent spectrum can be split into active and inactive flow structures. The large-scale engulfment phenomena actively prescribe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Despite the detailed research available, how entrainment is modified by the turbulent coherent structures is still needed for practical applications, such as large-eddy simulation and the low-order models for flows (Neamtu-Halic et al 2019;Cimarelli & Boga 2021). For small-scale structures, it has been observed that the λ-scaled vortex close to TNTI will modulate its nearby entrainment rate in both numerical and experimental studies (da Silva et al 2014a;Mistry et al 2019;Neamtu-Halic et al 2020), where λ is the Taylor microscale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the detailed research available, how entrainment is modified by the turbulent coherent structures is still needed for practical applications, such as large-eddy simulation and the low-order models for flows (Neamtu-Halic et al 2019;Cimarelli & Boga 2021). For small-scale structures, it has been observed that the λ-scaled vortex close to TNTI will modulate its nearby entrainment rate in both numerical and experimental studies (da Silva et al 2014a;Mistry et al 2019;Neamtu-Halic et al 2020), where λ is the Taylor microscale.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed multiscale analyses have been conducted by Philip et al (2014) and Mistry et al (2016): by filtering the flow field with varying filter size Δ, it is found that, although the tortuosity of TNTI and the instantaneous entrainment velocity vary in different Δ, the total entrainment flux is independent of Δ. More recently, the large-scale and small-scale velocity fields in a temporal jet were numerically separated and evolved independently (Cimarelli & Boga 2021). It was found that the entrainment is more violent in the large-scale velocity field, which again suggests the importance of large-scale motions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the entrainment is a multiscale process, which means that the large-scale motions are also involved (Mistry et al 2016). Some recent studies showed that the large-scale motions do modulate the entrainment velocity in the TBL (Long, Wang & Pan 2022) and jet (Cimarelli & Boga 2021). Furthermore, the large-scale motions are shown to dominate the mass and energy transport in the outer region (Adrian, Meinhart & Tomkins 2000) in TBL.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the entrainment becomes dominated by large-scale engulfment of background fluid under the influence of the coherent motions (e.g. Yule 1978; Bisset, Hunt & Rogers 2002; Cimarelli & Boga 2021; Long, Wang & Pan 2022). For TTIs, Kankanwadi & Buxton (2023) observed that both the turbulence intensity and the integral length scale in the ambient flow correlate to enhanced entrainment in the presence of the large-scale coherent vortices in the near wake of a cylinder – a contrasting result to the far-field study in which background turbulence was observed to suppress entrainment rate (Kankanwadi & Buxton 2020).…”
Section: Introductionmentioning
confidence: 99%